Doubled-Edged Swords in the Biology of Conflict - Sapolsky, Robert M. (Frontiers in Psychology, 2018)
Considerable advances have been made in understanding the biological roots of conflict, and such understanding requires a multidisciplinary approach, recognizing the relevance of neurobiological, endocrine, genetic, developmental and evolutionary perspectives. With these insights comes the first hints of biological interventions that may mitigate violence. However, such interventions are typically double-edged swords, with the potential to foster conflict rather than lessen it. This review constitutes a cautionary note of being careful of what one wishes for.